Neuroprotective Therapy for Stroke and Ischemic Disease - Lapchak, Paul A.; Zhang, John H. (Springer International Publishing : Imprint: Springer, 2017)
This book is a critical and comprehensive look at current state-of-the-art scientific and translational research being conducted internationally, in both academia and industry; it serves to address new ways to provide effective treatment to victims of ischemic and hemorrhagic stroke and other ischemic diseases. Currently, stroke can be successfully treated through the administration of a thrombolytic, but the therapeutic window is short and many patients are not able to receive treatment. Only about 30% of patients are "cured" by available treatments. Divided into five sections, the proposed volume explores historical and novel neuroprotection mechanisms and targets, new and combination therapies, as well as clinical trial design for some of the most recent bench-side research.
Keywords: Medicine.; Neurosciences.; Cardiology.; elektronické knihy; electronic books